2017
DOI: 10.14687/jhs.v14i3.4591
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of strategies for managing stress among muay thai sportsmen participating in intervarsity sports competitions<p>Üniversiteler arası spor müsabakalarına katılan muay thai sporcularının stres ile başa çıkma stratejilerinin değerlendirilmesi

Abstract: Sports competition is one of most intense occasions where stress is felt quite intensely. Fierce competition environment, expectations, psychological pressure, will to win, and anxiety about backfire, will undermine sportive performance. The main aim of this research is to determine different strategies that various muay thai sportsmen participating in sports competition among universities use in coping with stress. In order to measure the stress coping strategies of athletes, stress coping style scales adapte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Also, Kırtepe et al, (2017) did not find differences between the satisfaction levels based on the gender. Another survey that confirms our research results is the study of Eraslan et al, (2017). They mentioned that the female participants have higher point averages about overcoming the stress.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Also, Kırtepe et al, (2017) did not find differences between the satisfaction levels based on the gender. Another survey that confirms our research results is the study of Eraslan et al, (2017). They mentioned that the female participants have higher point averages about overcoming the stress.…”
Section: Discussionsupporting
confidence: 85%
“…In this research, there is found a positive relationship between age and aggression; a negative and insignificant relationship between the stress level and age variable. Eraslan et al (2017) mentioned that as the age level increases, there occurs a decrease in the scores of overcoming the stress. The reason for this circumstance may be the fear of losing and being exposed to the similar applications by the increase in age levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire items were adapted from earlier studies [3,8,13,[28][29][30]. One of the advantages in using the IS Success Factor Model and Hofstede Theory were that it had a well-validated measurement inventory.…”
Section: Methodsmentioning
confidence: 99%